Malta : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Malta. (IMF Staff Country Reports; Country Report, 2017)
This 2016 Article IV Consultation highlights an estimated nearly 4.1 percent expansion in Malta's output in 2016, following average growth of nearly 8 percent in 2014-15, supported by strong domestic demand. Robust job creation drove unemployment to record lows, despite a rising supply of labor, while subdued wage pressures contributed to low inflation. The external position remains strong, with sizable exports of services keeping the current account in surplus. The outlook is favorable, though growth is set to moderate to 3.4 percent in 2017 and converge to its potential of about 3 percent over the medium term following a projected weaker impetus from domestic demand.